Attitudes of mental health professionals towards alcohol use (Research, Society and Development, 2021)
Objective: to verify associations between the sociodemographic profile and the attitudes of professionals from a reference service on alcohol and other drugs, towards alcohol, alcoholics and alcoholism. Method: cross-sectional study carried out with 42 professionals from a service specialized in caring for users with disorders resulting from the use of alcohol and other drugs. For data collection, a sociodemographic questionnaire and the Scale of Attitudes towards Alcohol, Alcoholism and Alcoholism were applied. Univariate and multiple regression models were used to verify the association between outcomes. Results: positive attitudes were observed in the theoretical domains of work and the relationship established with the user, and negative attitudes towards alcohol use and its etiology. No associations were identified between sociodemographic variables and professional attitudes. Conclusion: attitudes towards alcohol, alcoholism and alcoholics are not associated with sociodemographic variables of health professionals in the context of a specialized service.